Qualitative Analysis of Pregnant Women with Preeclampsia at Muhammadiyah Ahmad Dahlan Hospital, Kediri - Respati, Laras Laxita Winda; Indasah, Indasah; Puspitasari, Yenny (Journal of Maternal and Child Health, 2024)
Background: Together with bleeding and infection included in the deadly triad, gestational hypertension affects 5-10% of pregnancies worldwide. Pre-eclampsia itself causes more than 70,000 maternal deaths and 500,000 fetal deaths. This study aimed to find significant predisposing factors that cause preeclampsia. Subjects and Method: Qualitative study with a phenomenological approach conducted at Muhammadiyah Ahmad Dahlan Hospital. The informants in this study were 15 pregnant women with preeclampsia. The focus of this research is to explore the predisposing factors for preeclampsia in pregnant women There are 4 research focuses related to pregnant women with preeclampsia, namely: (1) demographic data of pregnant women; (2) obstetric history; (3) nutrition; and (4) family health history. Data collection was carried out using interview techniques. The data collection were collected by interview techniques. Results: Pregnant women with preeclampsia were mostly housewives or low socio-economic, old and too young, obese, had families with a history of hypertension, were pregnant with different husbands. All of this can be detected using the preeclampsia screening sheet. Conclusion: Preeclampsia screening is performed periodically, to identify and diagnose the condition early, to allow for more careful monitoring and effective disease management.